EVALUATING THE SELF-CONCEPT OF JUVENILES HAVING DOWN SYNDROME THAT ARE PARTICIPATING IN A PROGRAM OF NATURE SPORTS (Fiep Bulletin - online, 2015)
This work had the main objective of develop nature sports practices among 23 students having Down Syndrome (DS) and to test their Self-concept. The realization of this study had comprehended 3 different phases: bibliographic research, application of the PAI (the perception test of the child`s Self-concept), and the elaboration and application of a program of nature sports (PEN). In the end of the program there have been the re-application of the PAI tests and it was made an analysis of the data results of the tests and of the impressions collected during the classes. It is possible to conclude that juveniles having DS show motor delays related to cognitive factors (of attention and comprehension), but they don`t present motor deficits. It was identified that a PEN can contribute in the improvement of the Self-concept of this population.
Keywords: Self-concept; Down Syndrome; Nature sports